Immune-mediated effects targeting hepatitis C virus in a syngeneic replicon cell transplantation mouse model. Issue 8 (23rd June 2017) - Levander, Sepideh; Holmström, Fredrik; Frelin, Lars; Ahlén, Gustaf; Rupp, Daniel; Long, Gang; Bartenschlager, Ralf; Sällberg, Matti
Abstract : Objective: HCV is characterised by its ability to establish chronic infection in hepatocytes and to replicate in the presence of an inflammation. We mimicked this situation in vivo in immune-competent mice by syngeneic transplantation of HCV replicon-containing mouse hepatoma cells. Design: A total of 5 million H-2 b positive Hep56.1D cells, carrying a subgenomic genotype (gt) 2a replicon (HCV replicon cells) or stably expressing comparable levels of the HCV NS3/4A protease/helicase complex (NS3/4A hepatoma cells), were injected subcutaneously into syngeneic H-2 b -restricted mice. Kinetics of tumour growth, HCV RNA replication levels and HCV-specific immune responses were monitored. For immune monitoring, new H-2 b -restricted cytotoxic T cell epitopes within the gt2a NS3/4A region were mapped. Immune mice were generated by DNA-based vaccination. Results: HCV replicon and NS3/4A hepatoma cells generated solid tumours in vivo. Similar to what is seen in human HCV infection did HCV RNA replicate in the presence of inflammation. NS3/4A-specific CD8+ T cells seemed to transiently reduce HCV RNA levels. Both CD4+ and CD8+ T cells were required for protection against tumour growth. Vaccine-induced NS3/4A(gt2a)-specific T cells protected against HCV replicon tumours in wild-type, but not in HCV NS3/4A(gt1a)-transgenic mice with dysfunctional HCV-specific T cells. Importantly, as in human HCV infection, HCV replicon cells neither primed nor boosted a strong NS3/4A-specific T cell response. Conclusion: Syngeneic transplantation of mouse HCV replicon cells into immune-competent animals mirrors many in vivo events in humans. This system is versatile and can be applied to any genetically modified H-2 b -restricted mouse strain.